2018
DOI: 10.1016/j.jtho.2017.11.132
|View full text |Cite
|
Sign up to set email alerts
|

Stromal PD-L1–Positive Regulatory T cells and PD-1–Positive CD8-Positive T cells Define the Response of Different Subsets of Non–Small Cell Lung Cancer to PD-1/PD-L1 Blockade Immunotherapy

Abstract: Our findings suggested that the density of PD-L1-positive CD4-positive CD25-positive Tregs in the tumor microenvironment can serve as a diagnostic factor to supplement PD-L1 expression in tumor cells and predict the response to PD-1/PD-L1 blockade immunotherapy in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 40 publications
3
94
0
Order By: Relevance
“…Various studies have indicated that tumor expression of PD-L1 predicts overall survival, PFS, and treatment responses in patients receiving immune therapy for advanced NSCLC. [31][32][33] Similarly, we found that strong PD-L1 expression predicted a poor response to EGFR-TKI therapy, consistent with a recent report by Soo et al 22 However, other investigators have drawn conflicting conclusions. Lin et al 34 reported an association of PD-L1 expression with better PFS in EGFR mutation-positive patients treated with EGFR-TKIs (16.5 versus 8.6 months (PD-L1-negative), p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Various studies have indicated that tumor expression of PD-L1 predicts overall survival, PFS, and treatment responses in patients receiving immune therapy for advanced NSCLC. [31][32][33] Similarly, we found that strong PD-L1 expression predicted a poor response to EGFR-TKI therapy, consistent with a recent report by Soo et al 22 However, other investigators have drawn conflicting conclusions. Lin et al 34 reported an association of PD-L1 expression with better PFS in EGFR mutation-positive patients treated with EGFR-TKIs (16.5 versus 8.6 months (PD-L1-negative), p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…These clinical features were faithfully recapitulated in early tumors in the orthotopic HKP1 model, leading us to utilize this model to target the PD-1/PD-L1 axis in early-stage lung cancer. Indeed, expression of PD-L1 in tumor cells and infiltrating immune cells and PD-1 in tumor-infiltrating T cells has been associated with responsiveness to blockade of the PD-1/PD-L1 immune checkpoint in NSCLC across the spectrum of the disease (8,9,(29)(30)(31)(32). Anti-PD-1 monotherapy yielded significant tumor control and improved survival in mice, which was associated with a robust antitumor immune response, as revealed by enhanced proliferation of T cell subsets and increased expression of effector cytokines by infiltrated CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating lymphocyte analysis of patients reveals that PD-1 þ CD8 þ T cells play a critical role in antitumor immune responses and that they could be a biomarker to predict antitumor responses of immune checkpoint inhibitors (10)(11)(12). However, systemic immune responses comprising of CD62L low CD44 þ CD69 þ CD90 þ CD27 low Tbet þ CD4 þ T cells are required to establish antitumor immunity and subsequently eradicate tumors in murine models (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CD4 þ T-cell help could enhance the cancer immunity cycle. CD4 þ T cells play an important role in antitumor immunity of murine models, and CD4 þ T cells that recognize cancer neoepitopes have been identified in melanoma (5,8,11,12). CD4 þ T cells in the peripheral blood correlate with clinical response to PD-1 blockade in patients with melanoma (13).…”
Section: Introductionmentioning
confidence: 99%